IMPROVING READING COMPREHENSION FOR STUDENTS’ VOCATIONAL HIGH SCHOOL THROUGH THE INTEGRATION OF DIGITAL STORYBOOK AND GRAPHIC ORGANIZERS - Putri Vania Sari; Arik Susanti (Wiralodra English Journal, 2026)
This study examined the effectiveness of digital storybooks and graphic organizers integrated with the ESP framework in enhancing narrative reading comprehension among vocational high school students in Digital Business field. Employing a quasi-experimental design, the study included 61 eleventh-grade students divided into experimental and control groups. Data were obtained from pre-test and post-test scores and analyzed through paired-sample and independent-sample t-tests. The experimental group, which received treatment, presented a significant mean score increase from 46.13 to 70.77, while the control group slightly improved from 41.50 to 50.63. These results indicate that the integration of digital storybooks and graphic organizers could effectively enhance students’ reading comprehension. Grounded in Multimedia Learning Theory and visual scaffolding, combining interactive digital tools with structured visual aids is an effective strategy for teaching narrative texts which support learners’ comprehension through multimodal input and structured visual representation. This research contributes to ESP pedagogy by demonstrating the integration of digital storybooks and graphic organizers within vocational Digital Business contexts supports narrative reading comprehension tailored to students’ occupational needs. Future studies could further explore the long-term impact of such tools, their application across different text genres, and their potential for enhancing other language skills.